Effect of High Fructose Syrup (HFS) Addition on Chemical and Organoleptic Properties of Green Coconut Water Kefir - Lita Lusiana Surja; Bambang Dwiloka; Heni Rizqiati (Journal of Applied Food Technology, 2019)
This research aims to determine the effect of High Fructose Syrup (HFS) addition to carbon dioxide (CO2) content, ethanol content and organoleptic properties of green coconut water kefir, and to determine the ideal HFS concentration for green coconut water kefir. Complete Randomized Design is used in this research with 5 treatments and 4 replications i.e. T0 (0% v/v HFS), T1 (2.5% v/v HFS), T2 (5% v/v HFS), T3 (7.5% v/v HFS), and T4 (10% v/v HFS). The CO2 content is measured by sodium carbonate (Na2CO3) titration, ethanol content is measured by distillation, while the organoleptic properties that included level of sourness, level of sweetness, soda sensation, sour aroma, and viscosity are done by 25 panelists. The results show that the addition of HFS is statistically gave significant effect to the CO2 content and organoleptic properties (P<0,05). However, the ethanol content, which analyzed using empirical model of quadratic polynomial regression, show that the addition of HFS is incompatible to the ethanol content of green coconut water kefir. The most optimal HFS concentration is 7.5% v/v, resulting CO2 content of 0.096%; ethanol content 1.545%; and desirable organoleptic properties, which are low level of sourness, high level of sweetness, very high soda sensation, low sour aroma, and high viscosity.